2014
DOI: 10.1016/j.joca.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rehabilitation programs for improving muscle strength in people with hip or knee osteoarthritis: a systematic review with meta-analysis

Abstract: To analyse the effect of exercise-based rehabilitation programs for improving lower limb muscle strength in individuals with hip or knee osteoarthritis (OA). A systematic search utilizing seven databases identified randomized controlled trials (RCTs) evaluating lower limb strength outcomes of exercise-based interventions for participants with hip or knee OA. All studies were screened for eligibility and methodological quality. Quality of evidence was assessed using Grading of Recommendation, Assessment, Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 68 publications
3
56
0
2
Order By: Relevance
“…Bridging this gap may provide evidence for innovative interventions that target hip adductors in people with knee OA, a strategy that to date remains untested. 45 Further research is also required to investigate hip strength deficits in the sagittal (flexion/extension) and transverse (internal/external rotation) planes. Only 1 study 25 investigated these actions isometrically, and 1 isokinetically, 10 with limited to moderate-quality evidence of weaker hip strength in people with knee OA.…”
Section: Measure/studymentioning
confidence: 99%
See 1 more Smart Citation
“…Bridging this gap may provide evidence for innovative interventions that target hip adductors in people with knee OA, a strategy that to date remains untested. 45 Further research is also required to investigate hip strength deficits in the sagittal (flexion/extension) and transverse (internal/external rotation) planes. Only 1 study 25 investigated these actions isometrically, and 1 isokinetically, 10 with limited to moderate-quality evidence of weaker hip strength in people with knee OA.…”
Section: Measure/studymentioning
confidence: 99%
“…17,38 Unknown are the optimal dose and type of exercise that would maximize outcomes over sustained periods. There are few studies that have evaluated targeted hip strengthening in knee OA as a management strategy 45 ; consequently, evidence to guide clinical decisions with regard to this is incomplete. The current review identified hip strength deficits that may potentially be targeted to optimize the outcomes of rehabilitation.…”
Section: Measure/studymentioning
confidence: 99%
“…Kalça ve diz OA hastalarında rehabilitasyon programlarının kas gücü üzerine etkinliğini değerlendiren metaanalizli bir sistematik derlemede diz OA konusunda çok sayıda çalışmaya değinilirken, kalça OA konusunda kas gücü üzerine etkiyi değerlendiren ve kontrol grubu içeren çalışma olmadığı belirtilmiş ve kısa dönem izlem içeren sadece bir çalışmaya yer verilmiştir (24). Bu çalışmada kalça abduksiyon gücü üzerine orta düzeyde etkinlik saptanırken ekstansiyon veya iç rotasyon üzerine belirgin bir etki saptanmamıştır (25).…”
Section: Kalça Osteoartriti (Oa)unclassified
“…Progressive leg muscle weakness contributes to pain, functional disability, and mobility limitations in persons with advanced stages of knee OA . Therefore, improving muscle strength by means of resistance exercises for the lower limbs is a major method of prevention and rehabilitation in patients with knee OA and has already shown beneficial effects …”
Section: Introductionmentioning
confidence: 99%